2004
DOI: 10.1038/nn1276
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic programming by maternal behavior

Abstract: Here we report that increased pup licking and grooming (LG) and arched-back nursing (ABN) by rat mothers altered the offspring epigenome at a glucocorticoid receptor (GR) gene promoter in the hippocampus. Offspring of mothers that showed high levels of LG and ABN were found to have differences in DNA methylation, as compared to offspring of 'low-LG-ABN' mothers. These differences emerged over the first week of life, were reversed with cross-fostering, persisted into adulthood and were associated with altered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

155
4,401
11
103

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 5,550 publications
(4,670 citation statements)
references
References 30 publications
155
4,401
11
103
Order By: Relevance
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Epigenetic modifications of the glucocorticoid receptor gene ( NR3C1 , referred to here as GR ) have also been associated with early‐life experiences in both rats and humans. Studies of early experiences in rats found that DNA methylation of the GR promoter region was altered by maternal care, which in turn was associated with GR expression and HPA responses to stress 12. In humans, stressful life events (e.g., trauma and abuse) have been associated with higher DNA methylation at the GR promoter region13, 14, 15, 16, 17, 18 as well as differential GR expression and biological markers of HPA‐axis activity, such as salivary cortisol 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…These epigenetic modifications occur without sequential variation. Epigenetic control of gene expression is highly responsive to environmental influences such as ELS, especially during developmentally sensitive periods in early life, as has been shown in rodents (Champagne, 2008; Meaney, 2001; Weaver et al, 2004) and humans (McGowan et al, 2009). DNA methylation, i.e., the attachment of methyl groups (CH 3 ) to the 5-carbon position of cytosine, which typically occurs at so-called CpG dinucleotides where a cytosine base is followed by a guanine base, generally results in gene silencing and is the only epigenetic modification of the human OXTR gene studied to date.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 94%
“…Animal studies revealed differential DNA methylation patterns within specific genes that are implied in stress-regulation (e.g., the GR coding gene) as a result of natural variations in early maternal care. These modifications appear to be highly persistent throughout the life span but are potentially reversible (Meaney, 2010; Weaver et al, 2004). Despite these well-established long-term effects of ELS on epigenetic regulation of specific genes, evidence for the stability of ELS-associated DNA methylation patterns across different developmental stages is lacking.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
“…ChIP experiments quantifying NF‐Yb binding to the Gria4 intronic regulatory region were performed in accordance with previously published methods (Weaver et al, 2004; Zhang et al, 2010). Briefly, Oli‐neu cells were plated at a density of 1 × 10 6 cells in T25 flasks and allowed to adhere overnight.…”
Section: Methodsmentioning
confidence: 99%